Eureka - Diehl, William (New York : Fawcett Books, 2003)
When Verna Wilensky is electrocuted in her bathtub, it appears to be a tragic accident, but as police detective Zeke Bannon looks deeper into her life, he finds a bank account full of money and reason to believe Verna might have been killed as a result of a blackmail scam.
Keywords: Police -- California -- Fiction; City and town life -- Fiction; Detective and mystery fiction